High-throughput screening of natural compounds for prophage induction in controlling pathogenic bacteria in food - Tompkins, Elizabeth; Cadieux, Brigitte; Amitrano, Margot; Goodridge, Lawrence (Frontiers in Food Science and Technology, 2023)
The prevalence of the clean label trend necessitates the development of natural approaches for controlling pathogenic bacteria that commonly contaminate food. The induction of prophages within the genomes of bacteria, which leads to their proliferation and subsequent host cell death, has been proposed as a new method to control pathogenic and spoilage bacterial growth in foods.In this study, a novel luminescence-based high-throughput assay was used to identify compounds that may serve as natural prophage-inducing agents. The assay was used to assess bioactive compounds from four chemical libraries (final concentration 10 µM) for their ability to induce prophages as measured by luminescence production in Escherichia coli BR513, a genetically engineered strain that produces β-galactosidase as a result of prophage λ induction. Relative light units (RLU) were normalized to cell concentration (as measured by optical density at a wavelength of 600 nm (OD600)) and to the interquartile mean of each respective 384-well plate. The cut-off of normalized RLU values that was used as an indicator of prophage induction for each replicate was set at 2.25 standard deviations above the mean of the data set. A positive hit for prophage induction was defined as a compound in which both replicate cultures generated normalized RLU values above their respective cut-off. Dose response experiments were conducted and confirmed that four naturally-derived compounds (osthol, roccellic acid, galanginee, and sclareol) were positive for prophage induction. These compounds, along with rosemary and gallic acid (which were previously identified as prophage inducers), as well as a selection of positive hits from the current assay, were included in dose response experiments in an attempt to determine ideal concentrations for prophage induction. The dose response results showed that the assay could not differentiate whether cell death occurred due to prophage induction or if the bacteria was killed by some other mechanism, and thus optimal concentrations for prophage induction could not be determined. The high-throughput luminescent prophage induction should nevertheless be considered a useful tool for the preliminary screening of natural bioactive compounds that may have the capacity to improve food safety and food quality through induction of prophages.